Summary report - IOC. International Coordination Group for the Southern Ocean, 2nd session, Buenos Aires, 1974; Intergovernmental Oceanographic Commission (1 Aug. 1974, 1974)
Meeting report on oceanographic research on the Southern ocean, including the Antarctic Ocean - Describes activities of working groups concerning the marine environment and marine resources, examines scientific cooperation in programmes for oceanographic data collection by means of artificial satellites and from ocean stations, includes the agenda of the meeting and provides summaries of national plans and programmes in the Southern Ocean